Critical discourse analysis of Cakna Diri: a module for sexual and reproductive health education for Malaysian parents - Ellin, Mohammed Rasheedan; Abdul Hamid, Siti Hazariah; Mohd Arifin, Siti Roshaidai; Hasan, Haliza; Othman, Sajaratulnisah; Mohd Zain, Norhasmah (2025)
This Critical Discourse Analysis (CDA) of the Cakna DiriModule explores how the parenting module, developed by Lembaga Penduduk dan Pembangunan Keluarga Negara (LPPKN), reflects and shapes power dynamics, ideologies, and social practices in the context of parenting sexualityin Malaysia. Utilizing Norman Fairclough’s CDA framework, the study examines how language constructs relationships of authority, conveys cultural and religious values, and communicates moral responsibilities related to SRH. The module emphasizes Islamic principles and conservative social norms, particularly regarding gender roles, sexuality, and parental guidance. Through analysis, the study highlights how the module frames issues such as pre-marital sex, boundaries, and family structures, while reinforcing parents' roles as moral gatekeepers. Furthermore, this CDA addresses how the module responds to societal concerns over youth behaviour, engaging with discourses of modernityand cultural identity in Malaysia. This analysis provides valuable input for improving SRHeducation approaches within the Malaysian socio-cultural and religious context